Об одном комплексе погребений Нетайловского могильника - Жиронкина, О.Ю.; Крыганов, А.В.; Цитковская, Ю.И. (My University, 1997)
Zhironkina O. Y., Kryganov A. V., Tsytkovskaya Y. I. Work at Netaylovsky Burial ground